1997
DOI: 10.2172/459884
|View full text |Cite
|
Sign up to set email alerts
|

Large scale traffic simulations

Abstract: DECLAIMERThis report was prepared as an account of work spotrsored by an agency of the United States Government. Neither the United States Government nor any agency thereof, nor any of their employees, make any warranty, express or implied, or as~mes any legal Iiability or responsibility for the accuracy, ampleten-or usefulness of any information, apparatus, product, or process disdosed, or represents that its use would not infringe privateIy. Abstract. Large scale microscopic (i.e. vehicle-based) traffic sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Using ideas from the theory of percolation phase transitions and the [12] cellular automata model (NaSch model) for numerical experiments, the critical exponent of jam durations was found to be very close to τ = 3/2 and suggested the relationship with the first return time of a one-dimensional random walk. Shortly after, the same authors [13] presented numerical evidence of SOC on a simple network and argued that conventional traffic control would tend to enlarge the area of the network under criticality. They suggested that an effective management strategy would be to force the system away from criticality through less efficient traffic management.…”
Section: Evidence Of Network Criticalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Using ideas from the theory of percolation phase transitions and the [12] cellular automata model (NaSch model) for numerical experiments, the critical exponent of jam durations was found to be very close to τ = 3/2 and suggested the relationship with the first return time of a one-dimensional random walk. Shortly after, the same authors [13] presented numerical evidence of SOC on a simple network and argued that conventional traffic control would tend to enlarge the area of the network under criticality. They suggested that an effective management strategy would be to force the system away from criticality through less efficient traffic management.…”
Section: Evidence Of Network Criticalitymentioning
confidence: 99%
“…Surprisingly, the impact of SOC in the field of traffic flow theory has been underwhelming [15,16]. Apart from [13,17,18] who present some numerical evidence of SOC on networks, it appears that the subject has gone largely under the radar. One reason might be that the main insight from the early works [6,10] was that SOC in the NaSch model emerges only in "cruise-control" mode, where random perturbations are only allowed in congested traffic states.…”
Section: Evidence Of Network Criticalitymentioning
confidence: 99%